The impact of air pressure on performance, combustion behavior, and emissions of an air-assisted port fuel injection HCCI engine - Dzulkafli, Mohd Firdaus; Hairuddin, Abdul Aziz; Al Anbagi, Muntasser Abdulabbas Mossa (Universiti Putra Malaysia Press, 2025)
Low-temperature combustion is achieved through homogeneous charge compression ignition (HCCI), which lowers the emission of nitrogen oxides (NOx) associated with diesel engines. HCCI combustion faces various obstacles, including combustion phasing, high hydrocarbon (HC) emissions, a limited operation range, and homogeneous mixture preparation. This research aims to compare the influence of air pressure in an air-assisted injector on performance, combustion behavior, and emissions. The experiment was conducted at an intake temperature of 50oC, speed of 2100 RPM and air pressures of 3,4 and 5 bar. Intake air was heated in an intake pipe heater, and an air regulator regulated the air pressure. An air assist pressure of 5 bar resulted in the highest brake thermal efficiency, ranging from 20.5% to 23.3%. For brake-specific fuel consumption, an air pressure 3 bar produced higher values ranging from 410.8 g/kWh to 500.8 g/kWh. The in-cylinder pressure for 3,4 and 5 bar pressure exceeds 80 bar at 25% load. Air pressure of 4 bar recorded the lowest HC, ranging from 50 to 75 ppm. For NOx emission, 3 bar air pressure showed the lowest levels, ranging from 8 to 12 ppm across the tested loads. The highest carbon monoxide (CO) percentage was recorded at 5 bar air pressure at 20% load with a CO value of 0.53%. At 20% and 25% load, the combustion profile displayed a three-stage ignition process, indicating the occurrence of diffusive combustion.